Traços e grupos funcionais do fitoplâncton na avaliação da redundância funcional e restauração lacustre em planícies de inundação. - Iatskiu, Patrícia (2021)
Biological communities derive not from a random distribution of organisms but are the result of many processes that include abiotic factors, biotic interactions, and dispersion. The impact of human activities has affected the structure and functioning of ecological communities at an accelerated pace. The phytoplankton community represents a major primary producer of aquatic environments, therefore factors that interfere with its structure and dynamics can also impact other trophic levels in the ecosystem. In this perspective, functional redundancy was the central theme of the first paper, whose aim was to investigate the response of redundancy in phytoplankton communities to environmental factors, when measured for functional groups and functional traits. For this, six years of data collected quarterly (2008 to 2013) from two temperate and three subtropical lakes were used. Traits and groups were efficient to measure this attribute, however, the traits were more efficient when the structuring process of the communities was the environmental filtering. The functional traits most effectively explain the relationship between redundancy and environment. In the second paper, the influence of hydrodynamics, landscape and resources on the structure of the phytoplankton community during a floodplain lake restoration process was evaluated. As expected, factors related to hydrodynamics and resources (light and nutrients) were determinants for biovolume and density. The relative importance of landscape to community attributes increased over time of restoration. Cyanobacteria were dominant at the beginning of the restoration process, followed by phytoflagellates and diatoms. Aiming to disseminate science, the third article presents basic concepts of phytoplankton ecology and the main results related to the themes of the two scientific papers. In summary, the functional approach in phytoplankton ecology stands out as an important tool for the development of community ecology and for restoration and management of aquatic ecosystems projects.